Analysis of the Anti-diabetic properties of Lactuca Sativa (l.) Seeds from diverse Geographical regions - Sayyed, Gaffar; Ingole, RD; kshirsagar, Nilesh V; Kale, PN; Abdul Azeem, Syed; S. Shirsat, Vibhuti; Garje, Sanjay; M. Nar, Akshay; B. Sanghai, Dhirendra; S. Padgilwar, Satish; et al. (Journal of Neonatal Surgery, 2025)
Lactuca sativa have been shown to have the potential to act as antidiabetic drugs, using diabetic rats as the subjects in the research that are currently being conducted. In the treatment of hyperglycemia and the prevention of metabolic problems associated with diabetes, these herbs have been shown to be effective. The utilization of Lactuca sativa for the treatment of diabetes has been employed for a considerable amount of time, and these findings lend credence to that approach. One possible reason for the reported antidiabetic effects could be that Lactucasativa can enhance the activity of pancreatic β-cells in the islets of Langerhans and increase their number. In order to ascertain the specific functions and areas of impact of these parts, as well as to evaluate the potential for synergistic effects between plant-derived products and synthetic medications, additional study is required to investigate the chemical components of the plant that are responsible for its hypoglycemic qualities. Different physicochemical properties, such as solid, semisolid, or liquid consistencies, can be included into topical formulations during the process of development. We are able to have a better understanding of the molecular pathways that are accountable for the affects that have been identified thanks to these investigations. The investigation of potential therapeutic targets follows the rapid identification and characterization of active molecules. Therefore, it will be less difficult to create a more potent and precise diabetes drug.